Cuproptosis and cuproptosis–related genes in rheumatoid arthritis: Implication, prospects, and perspectives - Zhao, Jianan; Guo, Shicheng; Schrodi, Steven J.; He, Dongyi (Frontiers in Immunology, 2022)
Rheumatoid arthritis (RA) is an autoimmune disease that severely affects patients’ physical and mental health, leading to chronic synovitis and destruction of bone joints. Although various available clinical treatment options exist, patients respond with varying efficacies due to multiple factors, and there is an urgent need to discover new treatment options to improve clinical outcomes. Cuproptosis is a newly characterized form of cell death. Copper causes cuproptosis by binding to lipid-acylated components of the tricarboxylic acid cycle, leading to protein aggregation, loss of iron-sulfur cluster proteins, and eventually proteotoxic stress. Targeting copper cytotoxicity and cuproptosis are considered potential options for treating oncological diseases. The synovial hypoxic environment and the presence of excessive glycolysis in multiple cells appear to act as inhibitors of cuproptosis, which can lead to excessive survival and proliferation of multiple immune cells, such as fibroblast-like synoviocytes, effector T cells, and macrophages, further mediating inflammation and bone destruction in RA. Therefore, in this study, we attempted to elaborate and summarize the linkage of cuproptosis and key genes regulating cuproptosis to the pathological mechanisms of RA and their effects on a variety of immune cells. This study aimed to provide a theoretical basis and support for translating preclinical and experimental results of RA to clinical protocols.